Designing learning object repositories as systems for managing educational communities knowledge - Sampson, Demetrios; Zervas, P. (2013)
Over the past years, a number of international initiatives that recognize the importance of sharing and reusing digital educational resources among educational communities through the use of Learning Object Repositories (LORs) have emerged. Typically, these initiatives focus on collecting digital educational resources that are offered by their creators for open access and potential reuse. Nevertheless, most of the existing LORs are designed more as digital repositories, rather than as systems for organizing and sharing educational communities' explicit knowledge (depicted in digital educational resources constructed by teachers and/or instructional designers) and tacit knowledge (depicted in teachers' and students' experiences and interactions of using digital educational resources available in LORs). Within this context, in this paper we present an approach for designing LORs as systems for facilitating the organization and sharing of different types of educational communities' knowledge.